Green technology of natural fiber reinforced bio-composites as alternative sustainable product - Hadibarata, Tony; Umarie, Winda; Voijant Tangahu, Bieby; Ramadhany, Putri; Ananda Putra, Gilang (Environmental and Toxicology Management, 2022)
Proactive strategies are being opted by metallurgical, foundry and manufacturing industries with respect to their experiences working with product designing based on product life cycle assessments. Without the consideration of the potential impacts on the life cycle, the development of new products would barely be sustainable. “Green” composites or bio-composites are fully degradable composites mainly consisting of a blend of biopolymer matrix and natural fibers which act as a reinforcing phase. In this study, natural bio-composite was reviewed as an alternative sustainable product. The types of natural fibers were also described as raw material of natural bio-composite. In addition, development natural fibers nowadays were mentioned. Furthermore, the application of natural fiber reinforced bio-composites was also presented.